Memanage Performance Karyawan Dengan Pemberian Kompensasi - Musringah, Musringah; Wicaksono, Eko (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2012)
For management, workers’ compensation issues may be a personnel issue is confusing and difficult. Although the basic wage should have a logical and defensible, it does cover a lot of emotional factors from the point of view of employees. However, in practice, the issue of compensation is always just a reference that can affect the performance or the performance of employees. Therefore, inevitably the company also needs to re-analyze the policies implemented in terms of compensation. This is solely to create a performance or a better employee performance, which in turn can also be a key to the success of the company in achieving the goals set earlier